PERMASALAHAN PENGEMBANGAN SUKUK KORPORASI DI INDONESIA MENGGUNAKAN METODE ANALYTICAL NETWORK PROCESS (ANP) - Endri Endri (University of Merdeka Malang, 2009)
This paper analyzed the problem of developing corporate sukuk in Indonesia using AnalyticNetwork Process (ANP) methodology, proceeded by literature survey and in-depth interviewwith scholars, practitioners, and regulator of Islamic capital market to fully understand the problemand to develop an appropriate ANP network. The cause of this problem could be grouped into fouraspects, namely 1) market player; 2) product characteristic; 3) regulation; and 4) government. Thisresearch found that the problems of developing corporate sukuk in Indonesia could be summed upinto two main causes from market player and regulation aspects, namely the lack of market playerunderstanding and quality of human resource which involved in Islamic capital market, and alsothe uncertainty of tax regulations. The suggested solution was to increase understanding of marketplayer by promoting Islamic capital market intensively, and then providing quality of human resourceby training and education comprehensively, revising tax regulation to avoid double taxation becomethe next solution. Other suggested solution from government aspect was to give support throughissuance sovereign sukuk. Moreover, the most effective policy strategy to overcome the problems ofIslamic capital market, specially in developing corporate sukuk market was by implementing marketdriven strategy, where policies were intended to make market mechanism running well.